2016
DOI: 10.4208/cicp.scpde14.44s
|View full text |Cite
|
Sign up to set email alerts
|

A New Weak Galerkin Finite Element Scheme for the Brinkman Model

Abstract: The Brinkman model describes flow of fluid in complex porous media with a high-contrast permeability coefficient such that the flow is dominated by Darcy in some regions and by Stokes in others. A weak Galerkin (WG) finite element method for solving the Brinkman equations in two or three dimensional spaces by using polynomials is developed and analyzed. The WG method is designed by using the generalized functions and their weak derivatives which are defined as generalized distributions. The variational form we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…The numerical method of [17] is based on the traditional gradient-divergence variational form for the Brinkman equations. In [24], we presented a new WG scheme based on the gradient-gradient variational form. It is shown that this scheme is suit for the mixed formulation of Darcy which would present a better approximation for this case.…”
mentioning
confidence: 99%
“…The numerical method of [17] is based on the traditional gradient-divergence variational form for the Brinkman equations. In [24], we presented a new WG scheme based on the gradient-gradient variational form. It is shown that this scheme is suit for the mixed formulation of Darcy which would present a better approximation for this case.…”
mentioning
confidence: 99%
“…Here we have used the assumption that the set of transition points from u = 0 and u > 0 on C is finite. Combining (28)- (30), and (32), we find that…”
Section: Lemma 24 Let U Be the Solution Of (1) It Holds Thatmentioning
confidence: 79%
“…The weak Galerkin (WG) method was initially proposed in [19] by Wang and Ye to solve second order elliptic equations. Later on, WG methods have been further developed to solve Helmholtz equations [20], biharmonic equations [21][22][23][24][25], Stokes equations [26,27], Brinkman problems [28][29][30], Maxwell equations [31] and other problems [32][33][34][35]. By using the weak derivative, the WG method allows for totally discontinuous functions of piecewise polynomials on partitions.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [10] gives a stable least-square formulation by introducing an auxiliary variable to substitute for velocity flux. Other more novel methods, such as weak Galerkin finite element method [11,12], multigrid method [13], and virtual method [14], are applied to Brinkman model without considering parameter dependence of solution.…”
Section: Introductionmentioning
confidence: 99%